Optimalisasi Potensi UMKM Melalui Legalisasi dan Digitalisasi untuk Meningkatkan Kualitas Usaha di Desa Wedung, Wedung, Demak, Jawa Tengah - Cahyo Wulandari; Abdurrahman Al Kholili; Anawinta Choirunnisa; Muhammad Mukhlas Cahyadi (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
This article discusses the program to optimise the potential of Micro, Small and Medium Enterprises (MSMEs) in rural areas through a series of strategies that include data collection, registration of business licences, product certification, and development of MSMEs through aspects of packaging, branding and digital marketing. These programs were held in Wedung Village, Wedung, Demak. This service program aims to improve the quality of MSME businesses in the area through concrete steps. Data collection and registration of business licences is the first step in providing a legal basis and legality for MSMEs. Product certification is directed at improving the quality standards of MSME products, so that they can access a wider market. In addition, developing MSMEs through attractive packaging and strong branding will help differentiate products from competitors and build a positive image in the eyes of consumers. Digital marketing is considered as an effective tool in expanding market reach and reaching potential customers through online platforms. Through this approach, this article explores concrete efforts to strengthen MSMEs in rural areas, which in turn are expected to increase the local economy, create jobs, and reduce economic disparities between regions. By integrating data collection, business licences, product certification, and development through aspects of packaging, branding and digital marketing, this article provides a holistic view of how MSMEs in Wedung Village can optimise their potential and improve business quality to be sustainable.